The relationship between metamotivational knowledge and performance - Ross, Jessica; Nguyen, Tina; Fujita, Kentaro; Miele, David B.; Edwards, Michael C.; Scholer, Abigail A. (Frontiers in Psychology, 2023)
Self-regulation research highlights the performance trade-offs of different motivational states. For instance, within the context of regulatory focus theory, promotion motivation enhances performance on eager tasks and prevention motivation enhances performance on vigilant tasks (i.e., regulatory focus task-motivation fit). Work on metamotivation—people’s understanding and regulation of their motivational states—reveals that, on average, people demonstrate knowledge of how to create such task-motivation fit; at the same time, there is substantial variability in this normative accuracy. The present research examines the psychometric properties of the knowledge assessment (Study S1) and whether having accurate normative metamotivational knowledge predicts performance (Studies 1-2). Results revealed that more accurate metamotivational knowledge predicts better performance on brief, single-shot tasks (Study 1) and in a consequential setting (course grades; Study 2). The effect was more robust in Study 2; potential implications of this variability are discussed for understanding when and why knowledge may be associated with performance.